Effects of Use of Proton Pump Inhibitors with Calcium Acetate on Serum Phosphorus Levels in Hemodialysis Patients - Deniz Çekiç; Savaş Sipahi; Mehmet Emir Arman (Babol University of Medical Sciences, 2023)
Background: The increase in serum phosphorus level is an independent risk factor for mortality in patients with chronic renal failure or undergoing dialysis due to end-stage renal disease. (1) Proton pump inhibitors (PPI) are the general name given to agents used to suppress stomach acid. In this study, the clinical benefit of using PPIs in addition to drugs used for phosphorus control was investigated. Methods: 153 patients with end-stage renal disease were included in the study. The data of the patients who had been on hemodialysis for at least 6 months and using calcium acetate for at least 1 month were recorded in the SPSS 21 program. The patients were analyzed in two groups according to whether they used PPI or not. Anamnesis, patient follow-up, laboratory, and treatment forms collected from hemodialysis centers were used. Results: Of the 153 patients in the study, 49% were males and the mean age was 65.11±11.23. The mean duration of patients on dialysis was 48.5 months. Hypertension was found to be the most common comorbidity with 75.8% prevalence among the patients. The mean phosphorus levels of the patients using calcium acetate together with PPI were found to be approximately 1.2 mg/dl lower (p= 0.000). Conclusion: It should be taken into account that the use of PPI together with calcium acetate, which is still common as a phosphorus binder in developing countries, can contribute to controlling phosphorus levels.